Hubungan Status Ekonomi dan Jumlah Kunjungan Antenatal Care (ANC) dengan Kejadian Kurang Energi Kronik (KEK) pada Ibu Hamil di Wilayah Kerja Puskesmas Donggo - Nur Titininingsih; Fidiya Rizka; Kristiani Murti Kisid (LPPM STIKES Mataram, 2023)
Introduction: Introduction: Chronic Energy Deficiency (CED). CED in pregnant women is a condition where the mother lacks protein and energy intake during pregnancy which can result in health problems for the mother and fetus. At the Donggo Community Health Center, it was found that the incidence of CED in pregnant women in 2021 was 52 pregnant women and increased in 2022. as many as 90 pregnant women out of a total of 439 pregnant women.. Objective: to determine the relationship between economic status and the number of Antenatal Care (ANC) visits with the incidence of Chronic Energy Deficiency (CED) in pregnant women in the Donggo Community Health Center working area. Methods: Method: The type of research used is descriptive analytical research. The population in this study were all pregnant women aged 27-40 weeks, totaling 56 pregnant women using total sampling technique. Descriptive analytical research design using the Spearman Rank test with the help of SPSS version 25.0. Result: Economic status has a significant relationship with Chronic Energy Shortage (KEK) Sig. 0.000 < 0.05). The number of Antenatal Care (ANC) visits did not have a significant relationship with the incidence of Chronic Energy Deficiency (CED) (Sig. 0.204 > 0.05). Conclusion: the results of the study concluded that economic status has a significant relationship with Chronic Energy Deficiency (CED) in pregnant women, while the number of Antenatal Care (ANC) visits is not related to Chronic Energy Deficiency (CED) in pregnant women in the Donggo Community Health Center working area.